2020
DOI: 10.1038/s12276-020-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

ROS in cancer therapy: the bright side of the moon

Abstract: Reactive oxygen species (ROS) constitute a group of highly reactive molecules that have evolved as regulators of important signaling pathways. It is now well accepted that moderate levels of ROS are required for several cellular functions, including gene expression. The production of ROS is elevated in tumor cells as a consequence of increased metabolic rate, gene mutation and relative hypoxia, and excess ROS are quenched by increased antioxidant enzymatic and nonenzymatic pathways in the same cells. Moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
1,003
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,577 publications
(1,159 citation statements)
references
References 167 publications
25
1,003
0
Order By: Relevance
“…H 2 O 2 induces oxidative stress in mammalian cells which signals the activation of several cellular pathways including of pro-inflammatory cytokine production and cell death or apoptosis (Pelaia et al, 2004 ; Valko et al, 2007 ; Forman et al, 2010 ; Vilema-Enriquez et al, 2016 ; Park, 2018 ; Aggarwal et al, 2019 ). H 2 O 2 acts as double-edged sword; while it is shown to be a potent carcinogen in normal cells (Lisanti et al, 2011 ), localized production of H 2 O 2 has been used in hyperoxygenation therapy for cancer treatment (Liu and Wang, 2015 ; Vilema-Enriquez et al, 2016 ; Mast and Kuppusamy, 2018 ; Perillo et al, 2020 ). Studies have also shown that cancer cells are more sensitive to H 2 O 2 than normal cells (Aykin-Burns et al, 2009 ) which has led to increased interest in exploring its therapeutic potential for cancer treatment including oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 induces oxidative stress in mammalian cells which signals the activation of several cellular pathways including of pro-inflammatory cytokine production and cell death or apoptosis (Pelaia et al, 2004 ; Valko et al, 2007 ; Forman et al, 2010 ; Vilema-Enriquez et al, 2016 ; Park, 2018 ; Aggarwal et al, 2019 ). H 2 O 2 acts as double-edged sword; while it is shown to be a potent carcinogen in normal cells (Lisanti et al, 2011 ), localized production of H 2 O 2 has been used in hyperoxygenation therapy for cancer treatment (Liu and Wang, 2015 ; Vilema-Enriquez et al, 2016 ; Mast and Kuppusamy, 2018 ; Perillo et al, 2020 ). Studies have also shown that cancer cells are more sensitive to H 2 O 2 than normal cells (Aykin-Burns et al, 2009 ) which has led to increased interest in exploring its therapeutic potential for cancer treatment including oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxidative stress induces the release of intracellular proteins through non-classical mechanisms [ 48 , 49 ] and it promotes exosome secretion from cancer cells [ 50 ]. Oxidative stress is a common feature of high proliferating cancer tissue and moderate levels of ROS and in particular, H 2 O 2 , directly impact on different aspects of cancer phenotype affecting signal transduction pathways [ 51 , 52 ]. Indeed, during cancer transformation low/moderate levels of ROS has been demonstrated to act as signaling molecules activating MAPK/ERK1/2 and AKT pathways and contributing to cancer cell proliferation, survival, and motility [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, during cancer transformation low/moderate levels of ROS has been demonstrated to act as signaling molecules activating MAPK/ERK1/2 and AKT pathways and contributing to cancer cell proliferation, survival, and motility [ 51 ]. On the opposite, a stronger and toxic oxidative stress would be deleterious also for cancer cells triggering, preferentially, a pro-apoptotic p38/MAPK pathway [ 52 ]. Of note, among the different signaling pathways affected by oxidative stress, evidence indicates that AKT signaling also contributes to the regulation of protein secretion through the non-classical pathway as reported for FGF-1 [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study in esophageal squamous cell carcinoma suggested that an increase in the SOD-2 levels resulted in resistance to cisplatin in the related cells [ 48 ]. ROS control is considered to be an effective cancer treatment method [ 49 ]. However, our data suggest that cellular uptake should be carefully considered, as it might have outcomes opposite to those intended.…”
Section: Discussionmentioning
confidence: 99%